Assessing the need for pre-mental health competencies in undergraduate education: insights from graduate faculty surveys - Blomquist, Kerstin K.; Wenze, Susan J.; Fleming, C. J. Eubanks; Ernestus, Stephanie M. (Frontiers in Psychology, 2024)
Despite the value of clinical competencies for masters- and doctoral-level practitioners as well as the tremendous variability in preparedness for graduate school and at graduation from graduate school, there are no competency standards for students pursuing mental health care careers prior to graduate study. This study aimed to identify potential pre-mental health competency standards for undergraduates pursuing mental health care careers. Faculty at masters and doctoral programs in a range of mental health care fields were asked to rate their expectations of entry-level competence and the perceived entry-level competence of their first-year, bachelor-level graduate students on 42 sub-competencies derived from the APA’s Competency Benchmarks in Professional Psychology. Faculty of both masters (N=320) and doctoral (N=220) programs reported high expectations of first-year graduate students for 11 competency categories (professional values/attitudes; relationships; management-administration; interdisciplinary systems; individual/cultural diversity; advocacy; scientific knowledge and methods; reflective practice, self-assessment, and self-care; ethical standards and policy; supervision, and research/evaluation) and 25 sub-competencies. Faculty in masters programs rated students as not meeting their expectations in 28 sub-competencies, while faculty in doctoral programs rated students as not meeting their expectations in 17 sub-competencies. Faculty recommended internships as well as improvement in writing, counseling skills, professional behavior, diversity, equity, and inclusion, cultural competence and humility, research methods, reading research, connecting research to practice, and education about the different mental health care professions. Our findings suggest that students would benefit from intentional training in multiple pre-mental health competency areas at the undergraduate level to facilitate graduate-level training in mental health care and to better prepare our future clinicians.